2012
DOI: 10.1038/nnano.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

A nanomechanical mass sensor with yoctogram resolution

Abstract: Nanomechanical resonators have been used to weigh cells, biomolecules and gas molecules, and to study basic phenomena in surface science, such as phase transitions and diffusion. These experiments all rely on the ability of nanomechanical mass sensors to resolve small masses. Here, we report mass sensing experiments with a resolution of 1.7 yg (1 yg = 10(-24) g), which corresponds to the mass of one proton. The resonator is a carbon nanotube of length ∼150 nm that vibrates at a frequency of almost 2 GHz. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
762
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 935 publications
(828 citation statements)
references
References 30 publications
6
762
0
6
Order By: Relevance
“…By comparing Equation (12) to Equation (8) and recalling that I max LF is defined as the low-frequency current when o drive matches the resonant frequency, we get…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing Equation (12) to Equation (8) and recalling that I max LF is defined as the low-frequency current when o drive matches the resonant frequency, we get…”
Section: Methodsmentioning
confidence: 99%
“…Its crystallinity confers excellent mechanical properties to nanotube-based resonators [1][2][3][4][5][6] , such as high resonant frequencies 7,8 and low dissipation at low temperature 9,10 . As a result, these resonators are well suited for ultra-sensitive detection of mass 11,12 , charge 2,3 and force 13 . A nanotube has also much in common with a polymer as both can bend by a large amount.…”
mentioning
confidence: 99%
“…Applications range from nanoscale detection of forces in the context of scanning probe microscopy 1 to molecular-recognition-based mass screening in the medical sciences 2 . The sensitivity of submicron-thick devices has progressed to a point where the attonewton force of single spins 3 or the mass of single molecules and proteins 4,5 can be measured in real time. Singly clamped cantilever beams have been pivotal in several fundamental physical discoveries, including the detection of persistent currents in normal metal rings 6 and the observation of half-height magnetization steps in Sr 2 RuO 4 (ref.…”
mentioning
confidence: 99%
“…Owing to their small size (on the scale of Angstroms) and the large energy gaps (on the scale of eV), transport through single molecules can remain phase coherent even at room temperature, and constructive or destructive quantum interference (QI) can be utilized to manipulate their room temperature electrical [10][11][12][13] and thermoelectrical 14,15 properties. In previous studies, it was reported theoretically and experimentally that the conductance of a phenyl ring with meta (m) connectivity is lower than the isomer with para (p) connectivity by several orders of magnitude [16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%